2016
DOI: 10.5194/hess-20-1459-2016
|View full text |Cite
|
Sign up to set email alerts
|

Global root zone storage capacity from satellite-based evaporation

Abstract: Abstract. This study presents an "Earth observation-based" method for estimating root zone storage capacity – a critical, yet uncertain parameter in hydrological and land surface modelling. By assuming that vegetation optimises its root zone storage capacity to bridge critical dry periods, we were able to use state-of-the-art satellite-based evaporation data computed with independent energy balance equations to derive gridded root zone storage capacity at global scale. This approach does not require soil or ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
221
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(229 citation statements)
references
References 78 publications
6
221
2
Order By: Relevance
“…Soil evaporation is limited by a complementary relationship hypothesis which defines land-atmospheric interactions from vapor pressure deficit and relative humidity [69]. Various ET comparison studies using MOD16 data have been undertaken, see for instance [32,39,70]. MOD16 ET was validated [71] using flux towers in South Africa, and found that ET was systematically underestimated by 7.5 to 26.3 mm per month, something confirmed by [72,73].…”
Section: Actual Evapotranspirationmentioning
confidence: 98%
“…Soil evaporation is limited by a complementary relationship hypothesis which defines land-atmospheric interactions from vapor pressure deficit and relative humidity [69]. Various ET comparison studies using MOD16 data have been undertaken, see for instance [32,39,70]. MOD16 ET was validated [71] using flux towers in South Africa, and found that ET was systematically underestimated by 7.5 to 26.3 mm per month, something confirmed by [72,73].…”
Section: Actual Evapotranspirationmentioning
confidence: 98%
“…Those measurements enable the estimation of root zone storage capacity [24], landscape heterogeneity, dominant runoff generating mechanisms [25,26], sub-surface storage fluctuation, and groundwater recession [27].…”
Section: Discussionmentioning
confidence: 99%
“…Within the six approaches classified by Wang-Erlandsson et al [115], for the estimation of root zone water storage capacity, RS-based studies are generally based on field observations and look up tables [116][117][118][119]. Nevertheless, some recent studies propose the optimization-calibration and inverse modelling approaches with diverse purposes.…”
Section: Coupling Modelsmentioning
confidence: 99%
“…Some approaches assimilate into the soil water balance models either water stress estimates based on canopy temperature [120,121] or ET estimates based on SEB models [93,113,116,122] in order to calibrate the fraction of water depleted derived from the water balance model. In slightly different approach, some authors propose the integration of actual ET values in order to calibrate the soil water balance model in terms of the root zone storage capacity [115,[123][124][125]. The rationale of these approaches is that any empirical approach to the plant water stress, or alternative formulations as those based on the canopy temperature, must be equivalent to the soil water stress, a stress index based on the parametrization of the soil properties [122].…”
Section: Coupling Modelsmentioning
confidence: 99%